2017
DOI: 10.1007/s10461-017-1684-y
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Covariates of Recent Sexual and Physical Violence Against HIV-Infected Outpatient Drinkers in Western Kenya

Abstract: Victimization from physical and sexual violence presents global health challenges. Partner violence is higher in Kenya than Africa. Violence against drinkers and HIV-infected individuals is typically elevated, so dual vulnerabilities may further augment risk. Understanding violence risks can improve interventions. Participants were 614 HIV-infected outpatient drinkers in western Kenya enrolled in a randomized trial to reduce alcohol use. At baseline, past 90-day partner physical and sexual violence were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…As described in many other low-income countries [10,3840], the prevalence of FSI in our study was significantly higher among women. African cultural practices and belief systems provide the social environment for men to consider women as a property [41].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As described in many other low-income countries [10,3840], the prevalence of FSI in our study was significantly higher among women. African cultural practices and belief systems provide the social environment for men to consider women as a property [41].…”
Section: Discussionsupporting
confidence: 85%
“…Among our study participants, 34% reported having ever had FSI (32% and 38% among men and women, respectively). Although our prevalence corresponds to the figures estimated for most SSA countries [10, 37,38] it is higher than the figures described for women in Kinshasa in the 2014 national Demographic and Health Survey (DHS), in which 16% of women reported having suffered sexual violence (the same frequencies described in the previous 2007 DHS) [16,33]. Many of our participants were attending a healthcare center for HIV VCT and therefore, it was a higher risk population, probably more likely to report risk behaviors than the general population.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations